Sistem Monitoring Suhu dan Kadar Air pada Mesin Pengering Padi Berbasis Internet of Things - Syaifurrahman Syaifurrahman; Ayong Hiendro; Abqori Aula (Jurnal Fisika Unand, 2024)
Paddy drying is an activity to remove the excess of water content within paddy to achieve a better rice quality during the grinding process. Farmers often determine water level based on experience, such as biting the rice, if the skin breaks, it means the rice is ready to be grinded. This research examines a monitoring system on a paddy drying machine in order to obtain a higher quality paddy to be made into rice. On the machine, there is a hearing element to raise the temperature of the drying tank. The rise of the temperature of the drying tank must be monitored to maintain that the temperature is always within the pre-determined threshold. The monitoring system uses DHT11 and SEN0308 sensors connected to ESP32 module as data processing center, before being displayed on an LCD indicator or a smart phone. Accuracy Test results for sensors show both sensor readings are above 90%. The temperature and water level data of the paddy during the drying process can be seen live on an LCD indicator or a smart phone as an accurate information.